Science and Technology In Islam - Khalid A.S. Al-Khateeb (2001)
Islamic epistemology is based on a central doctrine; Allah (swt) is the source of all knowledge. Three main sources arise there form viz. God’s teaching to Adam, Revelation (Qur’an and Sunnah), and Fitrah. The knowledge of Adam of was transmitted to his sons, and continues to flow down from one generation to another. Revelation being the word of God holds the truth, nothing but. The words of the Qur’an and their contexts contain the absolute and infinite knowledge. The Qur’an contains verses, which instigate the human mind to ponder on the wonders of the Universe form atoms to galaxies. It is a prime motive for scientific research. God taught man all what man knows, including science and technology. It is He who taught Adam the names of all things. It is He who taught Noah how to build ships, and taught Dawood how to use Iron to make shields and war equipment. It is He who facilities the powers and contents of nature for human benefit. Fitrah is an inborn faculty and great gif bestowed upon man. It is a formidable natural force. When its powers are released, the mind opens up to inspiration, whence great feats are accomplished. In the West it is left unleashed, in contrast with Islam which refines and controls it. Pure Fitrah leads to (Iman) and guides the soul towards good.